1994
DOI: 10.1128/aem.60.7.2415-2420.1994
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Distribution of cry -Type Genes of Bacillus thuringiensis Isolates from Taiwan

Abstract: Using PCR with a set of specific oligonucleotide primers to detect cryI-type genes, we were able to screen the cry-type genes of 225 BaciUlus thuringiensis soil isolates from Taiwan without much cost in time or labor. Some combinations of cry genes (the cry-type profile) in a single isolate were unique. We identified five distinct profiles of crystal genes from the B. thuringiensis soil isolates from Taiwan. The cry genes included cryL4(a), cryIA(b), crylA(c), cryIC, cryID, and cryIV. Interestingly, 501 B. thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
37
1
4

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 21 publications
5
37
1
4
Order By: Relevance
“…However, some of the cry1 genes were not detected in this study (cry1Ad, cry1E, cry1F and cry9A). Accordingly, these genes were the most uncommon in some studies or totally absent in other (Chak et al 1994;Kim et al 1998;Kim 2000;Arango et al 2002;Maduell et al 2002;Uribe et al 2003;Martínez et al 2005). Although cry1C gene is commonly associated with cry1D gene, the present study showed 16 isolates with cry1D but not cry1C.…”
Section: Discussioncontrasting
confidence: 47%
“…However, some of the cry1 genes were not detected in this study (cry1Ad, cry1E, cry1F and cry9A). Accordingly, these genes were the most uncommon in some studies or totally absent in other (Chak et al 1994;Kim et al 1998;Kim 2000;Arango et al 2002;Maduell et al 2002;Uribe et al 2003;Martínez et al 2005). Although cry1C gene is commonly associated with cry1D gene, the present study showed 16 isolates with cry1D but not cry1C.…”
Section: Discussioncontrasting
confidence: 47%
“…In accordance with the present results, previous reports have also found that collections of strains from different environments may differ in their cry genes content. For example, Bravo et al (1998) found that the distribution of cry1A, cry1B, cry1C and cry1D was more frequent than cry1E and cry1F, and Chak et al (1994) reported that cry1A, cry1C and cry1D were more abundant in B. thuringiensis from Taiwan. The distribution of three genes, cry1C, cry1D and cry1E, was found to be statistically different in both collections, being more common within the terrestrial strains.…”
Section: Discussionmentioning
confidence: 99%
“…PCR analysis, bioassays and serological identification of B. thuringiensis collections demonstrated the large diversity that can be found among naturally-occurring strains (Ben-Dov et al 1997;Bravo et al 1998;Ferrandis et al 1999). Bacillus thuringiensis strains isolated from different habitats and geographical locations differ in the occurrence and diversity of cry genes content (Chak et al 1994;Bravo et al 1998). Moreover, the correlation of the cry genes profiles with toxicity has been reported to be at least partially dependent on the serovar (Porcar et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…With this technique, insecticidal activity of B. thuringiensis strains may be -at least to some extentpredicted, and novel cry genes may be identified. Screenings of cry genes have been performed among collections from several parts of the world including Spain [9,20], China [12,26], Mexico [5], Colombia [25], Taiwan [7], Bolivia [10], Israel, Kazakhstan, and Uzbekistan [4], among others.…”
Section: Introduction *mentioning
confidence: 99%
“…Cerón et al[6] detected 19.5% of cry1 genes in a B. thuringiensis Mexican collection of 241 isolates. In a screening carried out in Taiwan, cry1 genes were found in 98.2% of the 225 isolates[7]. The occurrence of cry1 genes in a study of B. thuringiensis isolates from Israel, Kazakhstan, and Uzbekistan was 33.5 % among 72 isolates[4].…”
mentioning
confidence: 98%